The role of working memory in encoding the temporal structure of events in episodic memory: Evidence from a dual-task paradigm. - Leroy, Nathan; Majerus, Steve; D'Argembeau, Arnaud (Memory & Cognition, 2026)
Naturalistic events are represented in episodic memory as sequences of experience units (i.e., segments of prior experience) that are separated by temporal discontinuities, so that events are temporally compressed during memory replay. In the current study, we aimed to shed light on the interplay between the segmental structure of events and working memory (WM) resources in shaping this temporal structure of episodic memories. Participants watched a series of 1-min videos that contained many or few event boundaries (EBs), while for half of the videos, a concurrent task was simultaneously performed to reduce the availability of WM resources. After each video, the time needed to mentally replay the events was measured, and then the content of memories was verbally described. Results showed that the number of recalled experience units was higher for videos that contained many EBs, leading to a lower temporal compression rate. In addition, the number of recalled experience units was lower when a concurrent task was performed during event perception, particularly for videos that contained many EBs. These results suggest that both the segmental structure of events and WM resources contribute to the formation of experience units that constitute episodic memories, thereby shaping the temporal compression of events.